Difficult Airway Society guidelines for awake tracheal intubation (ATI) in adults. (14th November 2019) - Ahmad, I.; El‐Boghdadly, K.; Bhagrath, R.; Hodzovic, I.; McNarry, A. F.; Mir, F.; O'Sullivan, E. P.; Patel, A.; Stacey, M.; Vaughan, D.
Summary: Awake tracheal intubation has a high success rate and a favourable safety profile but is underused in cases of anticipated difficult airway management. These guidelines are a comprehensive document to support decision making, preparation and practical performance of awake tracheal intubation. We performed a systematic review of the literature seeking all of the available evidence for each element of awake tracheal intubation in order to make recommendations. In the absence of high‐quality evidence, expert consensus and a Delphi study were used to formulate recommendations. We highlight key areas of awake tracheal intubation in which specific recommendations were made, which included: indications; procedural setup; checklists; oxygenation; airway topicalisation; sedation; verification of tracheal tube position; complications; management of unsuccessful awake tracheal intubation; post‐tracheal intubation management; consent; and training. We recognise that there are a range of techniques and regimens that may be effective and one such example technique is included. Breaking down the key practical elements of awake tracheal intubation into sedation, topicalisation, oxygenation and performance might help practitioners to plan, perform and address complications. These guidelines aim to support clinical practice and help lower the threshold for performing awake tracheal intubation when indicated.